Pattern and Outcome of Pediatric Traumatic Head Injury at Tertiary Care Center of Nepal - Parajuli, Sudhir Raman; Kamarcharya, Balgopal; Prajuli, Angana; Maharjan, Sumi; Bhusal, Anil (Annapurna Journal of Health Sciences, 2025)
Introduction: In Nepal, traumatic brain injury (TBI) stands out as a significant contributor to both mortality and disability. Its incidence is estimated at 382 per 100,000 people, surpassing the global average of 369 per 100,000. In order to implement preventive measures against traumatic brain injuries, we require epidemiological evidence to inform our actions. The objective of this study was to investigate the causes, pattern and outcomes of traumatic brain injuries in children. Methods: This study was a descriptive study of all children (under 18 years of age) who presented with head injuries to the Emergency of Manipal teaching Hospital in Pokhara. Fifty-one pediatric head injury patients aged up to 17 years were studied from 1st August 2022 to 30th July 2023. Results: The results indicated that male to female ratio was 2:1 with fall from height accounted for 54.9% of head injury. Mild head injuries were most common requiring conservative treatment. Preventive measures should be taken to reduce the head injuries in such a young age group. Conclusion: In this study, falls account for the majority of the accidents, followed by road traffic accidents. Most injuries are superficial. However, a careful clinical examination combined with judicious CT scan can help the physician to separate mild head injury from severe and help in their management.